Aksi Penyuluhan Hipertensi Dan Diabetes Serta Pemeriksaannya Di MAN 1, MAN 2 Pessel Dan SMA 2 Pesisir Selatan - Sefrianita Kamal; Serdiani Serdiani; Sara Surya; Lusia Eka Putri; Wira Wahyudi Nandayasa; Fitri Anisa; Dian Permata Sari; Noval Romadhoni (Jurnal Pengabdian Masyarakat Dharma Andalas, 2026)
Hypertension, also known as high blood pressure, is a symptomless condition in which blood pressure in the arteries increases. A person is considered to have high blood pressure if while sitting their systolic pressure is ?140 mmHg or their diastolic pressure is ?90 mmHg, or both. The incidence of diabetes mellitus (DM) and hypertension shows high numbers worldwide. Diabetes mellitus (DM) is a metabolic disease with hyperglycemia symptoms caused by abnormalities in insulin action, insulin secretion, or both. Classic complaints of DM include polyuria, polydipsia, polyphagia, and unexplained weight loss. The diagnosis of DM can be made if there are classic DM complaints with a random plasma glucose test result ?200 mg/dL or a fasting plasma glucose test result ?126 mg/dL, or a 2-hour plasma glucose test result after OGTT ?200 mg/dL, or an HbA1c test result ?6.5% using a well-standardized method. Activities carried out at MAN 1, MAN 2 PESSEL, and SMA 2 Pesisir Selatan include providing counseling about hypertension and Diabetes as well as their examination. They also provide information regarding herbal medicine in handling these cases. The goal is for students to understand the dangers of hypertension and Diabetes so that they are selective in consuming food and maintaining their lifestyle.